Applying gender-based analysis plus to Employee Assistance Programs: A Canadian perspective. (2nd April 2020) - Bartram, Mary; Atanackovic, Jelena; Runnels, Vivien; Bourgeault, Ivy Lynn; Fournier, Chantal; Kovacina, Nikolina; Contant, Alain; MacDonald, Louis; Porteous, Nancy; Renaud, Ariane
Abstract: Both workplace mental health and gender equity issues are in the spotlight in Canada as they are internationally. Accordingly, it is timely for Employee Assistance Programs (EAPs) to systematically consider sex, gender, and intersecting identities. Four cross-cutting priorities emerged from a focused analysis of the literature: (1) targeted outreach to men and other priority populations, (2) enhanced gender and diversity training for EAP counselors, (3) digital EAP services to meet preferences beyond face-to-face counseling, and (4) performance and quality improvement of both the EAP process and outcomes. The implications of these are considered using a Canadian case example.